Surveillance study on the tolerability and safety of Flebogamma® DIF (10% and 5% intravenous immunoglobulin) in adult and pediatric patients. Issue 5 (25th August 2017) - Alsina, Laia; Mohr, Andreas; Montañés, Maria; Oliver, Xènia; Martín, Esperanza; Pons, Jaime; Drewe, Elizabeth; Papke, Jens; Günther, Georg; Chee, Ronnie; Gompels, Mark
Abstract: Direct comparisons of tolerability and safety of concentrated intravenous immunoglobulin (IVIG) versus less concentrated products are scarce. In this postauthorization, prospective, observational, multicenter study, a systematic comparison of 10% and 5% concentrations of Flebogamma® DIF IVIG was performed in both adult and pediatric patients treated with the studied IVIG products according to the approved indications under routine conditions. Dose of product administered, adverse events (AEs), physical assessments, laboratory tests, and concomitant therapy were analyzed. Patient recruitment in the 10% and 5% product groups was, respectively, 34 (32 analyzed, 13 of them children, receiving 130 IVIG infusions) and 35 (34 analyzed, receiving 135 IVIG infusions). Twenty‐four infusions (18.5%; 95% CI: 11.8, 25.1) with the 10% product and 3 (2.2%; 95% CI: −0.3, 4.7) with the 5% product were associated with potentially treatment‐related AEs ( P < 0.0001). Nine patients (28.1%) infused with the 10% product and 3 (8.8%) infused with the 5% product presented, respectively, 33 and 8 treatment‐related AEs (of which 7 and 6, respectively, were serious AEs, experienced by only three hypersensitive patients). The profile of AEs occurring with the infusion of 10% and 5% products were comparable. The most frequent treatment‐related AEs were headache ( n = 17, 3 patients; 15 episodes, 1 patient) and pyrexia ( n = 6, 4 patients). In conclusion, no unpredictable risk was detected for both Flebogamma DIF 10% and 5% concentrations, which were therefore deemed as safe and well‐tolerated IVIG in the studied population. The frequency of infusions associated with treatment‐related AEs was lower with the 5% concentration.